Young Children’s Connectedness to Nature: Profiles and Influencing Factors - Rochimah, Nur; Hasanah, Nur; Karnia, Nia; Riana, Nancy; Khoerunnisa, Tasyia (PIAUD Universitas Islam Negeri Sunan Kudus, 2026)
Young Children’s connectedness to nature is an important foundation for the development of pro-environmental attitudes and behaviors from an early age. Such connectedness cannot be separated from the role of the family as the child’s closest environment, particularly through family characteristics and parent participation in the environment. This study aims to describe mothers’ educational levels, parent participation in the environment, and young children’s connectedness to nature, as well as to analyze the influence of mothers’ education levels and parent participation in the environment on young children’s connectedness to nature. This study employed a cross-sectional design using a quantitative associative-causal approach and involved 167 parents of children aged 4 to 7 years in Karawang Regency, who were selected using simple random sampling. Data were collected using questionnaires measuring mothers’ educational levels, parent participation in the environment, and young children’s connectedness to nature, and were analyzed using descriptive statistics and multiple linear regression analysis. The results indicate that mothers’ educational levels were generally in the middle to high categories, while parent participation in the environment was at a moderate level. Young Children’s connectedness to nature was found to be in the moderate to high category, particularly in the aspects of enjoyment of nature and awareness of nature. The results of the regression analysis show that mothers’ educational levels have a positive effect on young children’s connectedness to nature; however, parent participation in the environment demonstrates a stronger and more significant influence. These findings emphasize that young children’s connectedness to nature is more strongly shaped by active parental involvement in environmental activities than by mothers’ educational background. This study provides important implications for the development of environmental education in early childhood by highlighting the role of families and direct parental involvement in children’s environmental experiences.